2022
DOI: 10.1039/d2cp01893d
|View full text |Cite
|
Sign up to set email alerts
|

Frustration-driven allosteric regulation and signal transmission in the SARS-CoV-2 spike omicron trimer structures: a crosstalk of the omicron mutation sites allosterically regulates tradeoffs of protein stability and conformational adaptability

Abstract: Dissecting the regulatory principles underlying function and activity of the SARS-CoV-2 spike protein at the atomic level is of paramount importance for the understanding mechanisms of virus transmissibility and immune...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 117 publications
1
16
0
Order By: Relevance
“…As mutations serve as markers of genetic variations, it is difficult to quantify their stability; however, mutational effects on the proteins’ general stability can be predicted. A recently published article has demonstrated this point, where the S protein mutations within Omicron variant have been found to play roles in allosterically regulating the stability, conformational flexibility and structural adaptability of the protein [28].…”
Section: Resultsmentioning
confidence: 99%
“…As mutations serve as markers of genetic variations, it is difficult to quantify their stability; however, mutational effects on the proteins’ general stability can be predicted. A recently published article has demonstrated this point, where the S protein mutations within Omicron variant have been found to play roles in allosterically regulating the stability, conformational flexibility and structural adaptability of the protein [28].…”
Section: Resultsmentioning
confidence: 99%
“…By examining conformational landscapes and the residue interaction networks in the SARS-CoV-2 Omicron spike protein structures, we have shown that the Omicron mutational sites are dynamically coupled and form a central engine of the allosterically regulated spike machinery that regulates the balance between conformational plasticity, protein stability, and functional adaptability. 141 MD simulations demonstrated an allosteric crosstalk within the RBD in the apo-and the ACE2 receptor-bound states. 142 Allosteric interactions between SARS-CoV-2 spike mutational sites were also confirmed in extensive MD simulations, suggesting that the interplay of spatially proximal local interactions and long-range communications between sites of escape mutations can represent an evolutionary strategy employed by the virus to modulate virulence of emerging SARS-CoV-2 variants.…”
Section: ■ Allosteric Regulation Models and Machine Learning In Struc...mentioning
confidence: 93%
“…These studies provided compelling evidence that the SARS-CoV-2 S protein can function as a functionally adaptable allosterically regulated machine that exploits plasticity of allosteric centers to fine-tune responses to antibody binding, where the experimentally confirmed regulatory hotspots correspond to the global mediating centers of the allosteric interaction networks (Figure ). By examining conformational landscapes and the residue interaction networks in the SARS-CoV-2 Omicron spike protein structures, we have shown that the Omicron mutational sites are dynamically coupled and form a central engine of the allosterically regulated spike machinery that regulates the balance between conformational plasticity, protein stability, and functional adaptability . MD simulations demonstrated an allosteric crosstalk within the RBD in the apo- and the ACE2 receptor-bound states .…”
Section: Allosteric Regulation Models and Machine Learning In Structu...mentioning
confidence: 99%
“…No reuse allowed without permission. conformational landscapes and dynamic interaction networks in the SARS-CoV-2 Omicron structures, we found that Omicron mutational sites can be dynamically coupled through short and long-range interactions forming an adaptive allosteric network that controls balance and tradeoffs between conformational plasticity, protein stability, and functional adaptability [83].…”
Section: Introductionmentioning
confidence: 93%
“…The enhanced MD simulations examined the stability of the S-D 614G variant showing that the mutation orders the 630-loop structure and allosterically alters global interactions between RBDs, forming an asymmetric and mobile down conformation and facilitating transitions toward up conformation [75]. Our previous studies revealed that the SARS-CoV-2 S protein can function as an allosteric regulatory machinery that is controlled by stable allosteric hotspots to modulate specific regulatory and binding functions [76][77][78][79][80][81][82][83]. By examining (which was not certified by peer review) is the author/funder.…”
Section: Introductionmentioning
confidence: 99%